Role of pioneer trees and stand structure in facilitating reclaimed limestone quarry regeneration - Yunanto, Tedi; Shiddiq, Asep M.I.; Suswanto, Suswanto; Megawati, Megawati; Wulansari, Ayu Ratna; Baroroh, Maryam Karomah; Wardani, Melly Kusuma; Choirunnisa, Jihan (Brawijaya University, 2026)
Mine reclamation is essential to restore the natural functions of an environment. This usually starts with the planting of pioneer plants to enhance soil and trigger ecological succession. But the choice of pioneer species can have a huge impact on natural regeneration. This study investigated the impact of different planted pioneer species and their stand characteristics on the composition and number of naturally regenerated tree seedlings in a reclaimed limestone quarry. This study surveyed 14 random circular plots (radius 17.8 m) and compared the existing stand properties (Basal Area and Mean Height) and the number of naturally regenerated tree seedlings in the understory. The planted pioneer species significantly affected seedling abundance and composition, with twenty-four species identified. Enterolobium cyclocarpum (Fabaceae) was considered to be a particularly effective nurse tree and provided 'islands of fertility' for different heterospecific seedlings. Other species were found to have very large autogenic regeneration or inhibitory effects. Multiple regression indicates that BA positively (b=48.51, p=0.0009) and Mean Height negatively (b=-17.27, p=0.00995) had an impact on seedling abundance (adjusted R²=0.627), and the total amount of seedling is compared to the light limitation by stand maturity and seedling density from 2017 to 2024. Potassium (K?) and clay content were significantly increased from 2017 to 2024. These findings highlight that a variety of pioneer species, including Fabaceae can be planted together with silvicultural interventions, including thinning to increase canopy structure, seedling recruitment, biodiversity and ecosystem recovery in post-mining sites